Can Reliability of Multiple Component Measuring Instruments Depend on Response Option Presentation Mode?. (June 2016) - Menold, Natalja; Raykov, Tenko
This article examines the possible dependency of composite reliability on presentation format of the elements of a multi-item measuring instrument. Using empirical data and a recent method for interval estimation of group differences in reliability, we demonstrate that the reliability of an instrument need not be the same when polarity of the response options for its individual components differs across administrations of the instrument. Implications for empirical educational, behavioral, and social research are discussed.